Vacuum systems for the TPS accelerator. (November 2015) - Hsiung, G.Y.; Hsueh, H.P.; Wu, L.H.; Chang, C.C.; Cheng, C.M.; Chan, C.K.; Yang, Y.C.; Lee, T.Y.; Huang, C.S.; Chang, C.H.; Huang, I.T.; Chang, S.W.; et al.
Abstract: The Taiwan Photon Source (TPS) is a 3 GeV third generation accelerator light source. The vacuum systems contain an electron storage ring (SR) of 518.4 m in circumference and a concentric booster (BR) of 496.8 m in circumference, linked with the transport lines one from the booster to storage ring (BTS) and the other from the linear accelerator to the booster (LTB). To ensure the highest stability of the electron beam in the storage ring, all the vacuum systems for the SR, BTS, and BR, have been baked to the ultrahigh vacuum (UHV). The aluminum vacuum chambers with the completely oil-free precise manufacturing process provide a lowest surface outgassing rate and lowest broadband impedance for accommodating the beam in stable. The combination of the triode ion pumps and the non-evaporable getter (NEG) pumps provides a superior pumping efficiency and the ultimate pressure < 5 nPa. The 24 arc-cell vacuum systems, each about 14 m in length, have been baked to the UHV and sealed in the laboratory prior to transport to the TPS tunnel for the installation. Other vacuum systems were installed and baked on site in parallel. After completing the installations, commissioning of TPS was started in August 2014. Highlights: The vacuum systems for the 3 GeV Taiwan Photon Source (TPS) are introduced. An entire oil-free manufacturing process for the aluminum beam ducts provides a lowest surface outgassing rate. The combination of ion pump and NEG pump are used for pumping to the ultimate pressure <5 nPa. After completing the installations, the commissioning of TPS then started since August 2014.